Syncretic Cultural Multivocality and the Malaysian Popular Musical Imagination - Shanthini Pillai (Kajian Malaysia, 2013)
This article discusses modes of expression in selected contemporary Malaysian popular songs and music videos in English. The article argues that such audiovisual engagements can be best described as productions of syncretic cultural multivocality. First, the fusion of the multiple musical styles that inundated Malaysia's novel popular music industry in the 1950s is traced. Next, the development of a creative pop multivocality in contemporary Malaysian "hip hops" is described. The article proceeds primarily by reading the Malaysian popular music scene as a cultural text and demonstrates that although the history of Malaysian popular music reflects pop cosmopolitanism, the cultural multivocality that characterises the Malaysian identity resonates as powerfully (if not more powerfully) at the core of the nation's popular imagination. The article concludes that the skilful integration of various influences from global popular culture creates a musical palimpsest that is and will continue to be imprinted with a multitude of signifiers of syncretic cultural multivocality.